Timing of Delivery in Gestational Diabetes Mellitus: Need for Person-Centered, Shared Decision-Making. Issue 2 (June 2016) - Kalra, Bharti; Gupta, Yashdeep; Kalra, Sanjay
Abstract Gestational diabetes mellitus (GDM) is a medical as well as obstetric challenge, which needs person-centered management. The timing of delivery of women with GDM is discussed by various obstetric professional bodies. We highlight pertinent medical, obstetric, and psychosocial factors which may influence the timing of delivery in women with GDM. This commentary proposes a person-centered approach to decide the delivery timing in GDM and supports shared decision-making based upon the individual's biopsychosocial characteristics and environmental factors.